Skeletal remains of the oldest known pseudocoracid shark Pseudocorax kindlimanni sp. nov. (Chondrichthyes, Lamniformes) from the Late Cretaceous of Lebanon. (September 2021) - Jambura, Patrick L.; Stumpf, Sebastian; Kriwet, Jürgen
Abstract: A new fossil mackerel shark, Pseudocorax kindlimanni sp. nov. (Lamniformes, Pseudocoracidae), is described from the Cenomanian Konservat-Lagerstätte of Haqel, Lebanon. The new species is based on the most complete fossil of this group to date, which comprises an associated tooth set of 70 teeth, six articulated vertebral centra, numerous placoid scales and pieces of unidentifiable mineralized cartilage. The dentition of P. kindlimanni sp. nov. is marked by a high degree of monognathic heterodonty but does not exhibit the characteristic "lamnoid tooth pattern" known from other macrophagous lamniform sharks. In addition, P. kindlimanni sp. nov. shows differences in tooth microstructure and vertebral centrum morphology compared to other lamniform sharks. These variations, however, are also known from other members of this order and do not warrant the assignment of Pseudocorax outside the lamniform sharks. The new fossil is the oldest known pseudocoracid shark and pushes the origin of this group back into the Cenomanian, a time when lamniform sharks underwent a major diversification. This radiation resulted not only in high species diversity, but also in the development of a diverse array of morphological traits and adaptation to different ecological niches. Pseudocorax kindlimanni sp. nov. was a small, active predator capable of fast swimming, and it occupied the lower trophic levels of the marine food web in the Late Cretaceous. Highlights: Description of a new lamniform shark Pseudocorax kindlimanni sp. nov. from the Cenomanian of Haqel (Lebanon). Dental pattern, tooth histology and vertebral morphology differs from many other lamniform sharks. The new species represents the oldest known pseudocoracid shark, dating back the origin of this family to the Cenomanian. Pseudocorax kindlimanni sp. nov. was a small shark occupying the lower trophic levels in the Late Cretaceous marine food web.